Prevalence of Vitamin D Deficiency in Newly Diagnosed Multiple Myeloma Patients: Vitamin D in Myeloma Patients - Rizvi, Rija Shadab; Ali, Syeda Mah; Raza, Naila; Dawood, Sidra; Parveen, Shehla (Pakistan Journal of Health Sciences, 2025)
Multiple Myeloma (MM) is a plasma cell disorder with skeletal complications. Vitamin D deficiency may contribute to these complications. Objective: To check vitamin D levels and determine the prevalence of Vitmain D deficiency in newly diagnosed MM patients. Methods: A prospective cross-sectional study was conducted from July 2024 till February 2025 at Liaquat National Hospital, Karachi, including 85 newly diagnosed MM patients. Serum 25-hydroxyvitamin D (25(OH)D) levels were measured. Demographic and laboratory data, including hemoglobin, calcium, creatinine, LDH, uric acid, and serum protein electrophoresis, were collected. Blood samples for vitamin D analysis were collected in red-top tubes. All the data analysis was done by IBM SPSS Version 22.0. Results: A total of 85 newly diagnosed MM patients (mean age: 55 ± 8.6 years) were evaluated for vitamin D deficiency. Males comprised 54 (63.5%) patients, while females accounted for 31 (36.5%). The mean vitamin D level was 21.79 ± 7.2ng/mL. 56 (65.9%) of the patients had Vitamin D deficiency (<20ng/mL), 22 (25.9%) had insufficiency (20–29ng/mL), and only 7 (8.2%) had sufficient levels (≥30ng/mL). Urban residents had significantly lower vitamin D levels than rural residents (p = 0.03). Conclusions: Vitamin D insufficiency was prevalent in newly diagnosed MM patients and may contribute to skeletal complications. Variations in vitamin D levels based on patient residence suggest further investigation into potential contributing factors.